2021
DOI: 10.3389/fonc.2021.588101
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of IGF2BP1 and Its Targets as Potential Biomarkers in ETV6-RUNX1 Positive B-Cell Acute Lymphoblastic Leukemia

Abstract: Around 85% of childhood Acute Lymphoblastic Leukemia (ALL) are of B-cell origin and characterized by the presence of different translocations including BCR-ABL1, ETV6-RUNX1, E2A-PBX1, and MLL fusion proteins. The current clinical investigations used to identify ETV6-RUNX1 translocation include FISH and fusion transcript specific PCR. In the current study we assessed the utility of IGF2BP1, an oncofetal RNA binding protein, that is over expressed specifically in ETV6-RUNX1 translocation positive B-ALL to be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…We had earlier reported the overexpression of IGF2BP1 by RT-qPCR in the bone marrow of patients belonging to the ETV6::RUNX1 subtype in a cohort of Indian patients ( n =114) [ 28 ]. Additional samples were added to the same cohort (Total n =167).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We had earlier reported the overexpression of IGF2BP1 by RT-qPCR in the bone marrow of patients belonging to the ETV6::RUNX1 subtype in a cohort of Indian patients ( n =114) [ 28 ]. Additional samples were added to the same cohort (Total n =167).…”
Section: Resultsmentioning
confidence: 99%
“…Cdkn2a loss , alterations of Epor, Ebf1, Jak1, Jak3, Il2rb, Stat5 and Trp53 have all been shown to synergize with ETV6::RUNX1 to cause leukemia in mice [ 10 , 42 , 43 , 47 ]. We had previously identified that the RBP IGF2BP1 was specifically overexpressed in the ETV6::RUNX1 translocated B-ALL and validated the same in a larger cohort [ 28 ]. The importance of RBPs in the pathogenesis of various leukemias including the IGF2BP family is slowly being dissected [ 48 ].…”
Section: Discussionmentioning
confidence: 96%
“…Discontinuation of L-asparaginase and poor response to prednisolone is associated with poor outcomes in ETV6::RUNX1-positive pediatric B-ALL patients, indicating drug insensitivity [53]. Autophagy inhibition [54], spleen tyrosine kinase (SYK) [55], and IGF2BP1 [56] are potential future therapeutic targets for ETV6::RUNX1-driven B-cell precursor acute lymphoblastic leukemia due to their roles in ETV6::RUNX1 cell survival and prognosis. Through RNA-seq, we can identify upregulated and activated pathways at diagnosis and design combination chemotherapeutics to sensitize resistant primary cells to conventional drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, a previous study reveals that EGFL7 serves as a potential diagnostic marker in B-cell acute lymphoblastic leukemia (B-ALL) patients [17]. Another recent study displays that EGFL7 is overexpressed in AML patients compared to controls, and its overexpression relates to lower complete remission rates in AML patients [8].…”
Section: Discussionmentioning
confidence: 99%